4D-actuators by 3D-printing combined with water-based curing. (March 2022) - Mazurek-Budzyńska, Magdalena; Behl, Marc; Neumann, Richard; Lendlein, Andreas
Abstract: The shape and the actuation capability of state of the art robotic devices typically relies on multimaterial systems from a combination of geometry determining materials and actuation components. Here, we present multifunctional 4D-actuators processable by 3D-printing, in which the actuator functionality is integrated into the shaped body. The materials are based on crosslinked poly(carbonate-urea-urethane) networks (PCUU), synthesized in an integrated process, applying reactive extrusion and subsequent water-based curing. Actuation capability could be added to the PCUU, prepared from aliphatic oligocarbonate diol, isophorone diisocyanate (IPDI) and water, in a thermomechanical programming process. When programmed with a strain of ε prog  = 1400% the PCUU networks exhibited actuation apparent by reversible elongation ε' rev of up to 22%. In a gripper a reversible bending ε' rev(bend) in the range of 37–60% was achieved when the actuation temperature ( T high ) was varied between 45 °C and 49 °C. The integration of actuation and shape formation could be impressively demonstrated in two PCUU-based reversible fastening systems, which were able to hold weights of up to 1.1 kg. In this way, the multifunctional materials are interesting candidate materials for robotic applications where a freedom in shape design and actuation is required as well as for sustainable fastening systems. Graphical Abstract: ga1 Highlights: A novel multifunctional ink for 3D-printing, in which the actuator functionality is implemented in the shaped body functionality is demonstrated. The capability of this ink was validated by additive manufacturing and by injection molding. 4D-actuators were could be realized combining reversible actuation with the freedom in shape design by additive manufacturing.